Nucleosomes occurring in protein-free hybridoma cell culture. Evidence for programmed cell death - Franĕk, F; Dolníková, J (FEBS letters, 1991)
In addition to monoclonal immunoglobulin, two kinds of nucleoproteins, NP1 and NP2, were isolated from the supernatants of hybridoma cultures set up in a protein-free medium. As shown by SDS-electrophoresis the two nucleoproteins shared a set of proteins (apparent Mr 11,000 to 15,000), and differed in the DNA moiety (approximately 150 bp in NP1, approximately 350 bp in NP2). The amino acid composition of the protein moiety confirmed the nucleosomal origin of NP1 and NP2. The findings support the view that in hybridoma cultures the cells undergo death by apoptosis, i.e. a programmed process characterized by initial fragmentation of chromatin.
Keywords: molekulová hmotnost; aminokyseliny; viabilita buněk; Nucleoproteins; Molecular Weight; Cell Survival; Chromatography, Gel; Hybridomas; nukleozomy; nukleoproteiny; Nucleosomes; kultivované buňky; Animals; zvířata; hybridomy; gelová chromatografie; myši; DNA; Cells, Cultured; Mice; Amino Acids